2020
DOI: 10.3390/ma13051197
|View full text |Cite
|
Sign up to set email alerts
|

Using Fatigue Characteristics to Analyse Test Results for 16Mo3 Steel under Tension-Compression and Oscillatory Bending Conditions

Abstract: In this study, 16Mo3 steel was analysed for fatigue tests under tension-compression and oscillatory bending conditions. The analysis involved a comparison of fatigue test results obtained using the Manson-Coffin-Basquin, Langer and Kandil models and the models proposed by Kurek-Łagoda. It was observed that it is possible to substitute the basic tension-compression test performed in large testing machines with oscillatory bending tests carried out on a simple, modern test stand. The tests were performed under o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Also, properties of the Inconel layer or the interface between layer and base materials (Fig. 1) is a focus of many research articles [1,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, properties of the Inconel layer or the interface between layer and base materials (Fig. 1) is a focus of many research articles [1,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies on bending fatigue testing in the LCF regime have been conducted to evaluate the size effect and the influence of strain gradient on fatigue failure life. Kulesa et al [9], Kurek et al [10], and Kurek [11] developed a lab-made bending testing apparatus to conduct strain-controlled cyclic bending and evaluated the relationship between fatigue failure life and total strain amplitude. They demonstrated that the fatigue life of bending specimens was slightly longer than that of T/C specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the tests were performed phase-aligned with controlled values of bending and torsional moments amplitudes (dynamic load) [23][24][25][26][27]. Testing of materials subjected to bending and torsional loads, with controlled kinematic load, is much less common; however, some studies [28,29] analyzed essentially aligned kinematic loads causing bending and torsion. Literature sources on material testing in both possible load control variants (dynamic and kinematic) is lacking.…”
Section: Introductionmentioning
confidence: 99%